Prevalence and molecular epidemiology of extended spectrum β-lactamase producing Escherichia coli from hospital and community settings in Egypt - Mohamed Metwally Abdel-Moaty, Walaa Saeed Mohamed, Saeed Mohamed Abdel-All, Hoda Hamed El-Hendawy (Journal of Applied Pharmaceutical Science, 2016)
The prevalence and molecular epidemiology of Escherichia coli that produce extended spectrum β-lactamase (ESBL) in Cairo, Egypt was investigated. Ninety E. coli isolates were collected along the period of September to November 2012 from hospital and community settings. Antibiotic susceptibility of the E. coli isolates was determined by disk diffusion method. All isolates were screened phenotypically for ESBL production by combination disk method. The presence of blaCTX-M-I, blaCTX-M-IV, blaTEM and blaSHV genes in ESBL-producing E. coli was examined by PCR and sequencing experiments. The results showed high prevalence of ESBL-producing E. coli, 52% of the collected isolates were ESBL producers. The ESBL-producing isolates significantly (P < 0.05) had increased resistance compared with non–ESBL producers to cefuroxime, cefotaxime, ceftazidime, cefepime, ciprofloxacin, and co-trimoxazole. Imipenem was the most effective drug against ESBL producing isolates. All ESBL producing E. coli isolates were multi drug resistant (MDR) to eight antibiotics or more. Detection of ESBL genes in selected MDR-ESBL producing E. coli revealed that blaCTX-M-I was the most prevalent ESBL type. It is clear that the prevalence of ESBL producing E. coli in Cairo, Egypt is alarming high. This study is useful for clinician in order to improve the empiric treatment.
Keywords: Extended spectrum &beta; -lactamase, ESBL, E. coli, PCR, CTX-M.